The Sexual Behavior of Male Sexual Partner of Tranvestite in the Prevention Efforts of HIV/AIDS Transmission (KEMAS: Jurnal Kesehatan Masyarakat, 2016)
Transvestite is one of the high risk groups in HIV/AIDS. Integrated Biological and Behavioral Surveillance (IBBS) states that in 2011, the HIV prevalence among waria in Indonesia has reached 22%, increasing from 2009 (18.96%). Such occurrence is because transvestite usually has multiple partners in intercourse both oral and anal sex, and rarely use condoms. Similarly, the male regular partners of transvestite also have sex with multiple sexual partners. Therefore, they also have a high risk of spread of HIV/AIDS. The objective of this study is to analyze sexual behavior of male regular partner of transvestite in Efforts to prevent the spread of HIV/AIDS. The study was carried out in 2014 using qualitative approach. Data was collected by in-depth interview on 6 male regular partner of transvestite through purposive sampling and triangulation informants of peer educators. The result shows that the use of condom on male regular partners of transvestite is still low and they inconsistently use when having sex with transvestite, female sex workers and female girlfriend. Their knowledge about HIV/AIDS is not good, and some regular partner of transvestite also felt susceptibility to contracting HIV. However, the perceived severity and perceived of benefits male regular partner of transvestite is good about HIV /AIDS despite the barrier of perceived and perceived self-efficacy is low related  access to condoms.